The Relationship Between Humans and Technology: Society 5.0 & the Fourth Industrial Revolution - Fasanti Oktavia Laila Nandita; Dina Amalia Hadaninggar; Rahma Eka Ariyanti; Dita Ambarwati; Talita Salwa Salsabila; Bakhtiyar Zulmi; Alifiana Cahyani; Muhammad Mirza Ilyas; Arif Widagdo (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid advancement of digital technologies has transformed social, economic, educational, and cultural systems, generating new patterns of interaction between humans and technology within the contexts of Industry 4.0 and Society 5.0. This study aims to examine the dynamics of human–technology relationships, analyze the conceptual foundations linking Industry 4.0 and Society 5.0, and identify the strategic role of human agency in responding to technological transformation. A non-empirical qualitative design was employed through a literature review approach, utilizing scholarly articles, academic books, conference proceedings, and policy documents selected based on relevance, credibility, and conceptual alignment with the research objectives. Data were analyzed using qualitative content analysis involving thematic categorization, synthesis, and critical interpretation. The findings indicate that technology has evolved from a supporting instrument into an integral component of contemporary social life, while Society 5.0 expands the technological orientation of Industry 4.0 by emphasizing human-centered innovation and social well-being. Human agency emerges as the key determinant in ensuring that technological advancement contributes to ethical, inclusive, and sustainable development. The study highlights the importance of integrating digital competence, humanistic values, and adaptive capacities in shaping future digital societies.